2001
DOI: 10.1046/j.1365-2672.2001.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the ensiling process of corn and wheat

Abstract: Aims: The purpose of this work was to study the effect of temperature on the ensiling process and aerobic stability of corn and wheat silages. Methods and Results: The crops were ensiled in 1á5 l anaerobic jars, with and without an inoculant, at room or elevated temperatures (37±41°C). After two months of ensiling, the silages were subjected to an aerobic stability test at room and elevated (33°C) temperature. The results indicate that ensiling at elevated temperatures resulted in higher pH values, less lactic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 9 publications
3
51
2
5
Order By: Relevance
“…However, the number of epiphytic LAB on fresh crops is often very low, and this phenomenon was also evident in the present study (<10 5 cfu/g FM; Table 2). Additionally, ensiling is a fermentation process involving microbiological and enzymatic activity that is influenced by temperature [3]. In our study, the low lactic acid content, and high pH and AN/TN were observed in the corresponding controls at three different temperatures (Table 3, Figure 2).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…However, the number of epiphytic LAB on fresh crops is often very low, and this phenomenon was also evident in the present study (<10 5 cfu/g FM; Table 2). Additionally, ensiling is a fermentation process involving microbiological and enzymatic activity that is influenced by temperature [3]. In our study, the low lactic acid content, and high pH and AN/TN were observed in the corresponding controls at three different temperatures (Table 3, Figure 2).…”
Section: Discussionmentioning
confidence: 51%
“…As a result, the pH decreases and the forage is preserved [3]. The success of the ensiling process depends, to a great extent, on the epiphytic LAB present in the crop, and it is common to improve the silage quality by application of inoculants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A média de temperatura encontrada no topo do silo foi de 31º C, enquanto na base foi de 28ºC. Segundo Weinberg et al (2001), durante os estágios iniciais da fermentação, quando ainda há presença de ar residual entre as partículas da forragem, a temperatura pode chegar aos 40ºC, efeito causado pela respiração da planta e atividade de microrganismos aeróbios. Outras situações de aumento de temperatura acontecem quando a massa ensilada é exposta ao ar em função de uma vedação ineficiente e durante o descarregamento do silo.…”
Section: Temperatura E Ph Da Silagemunclassified
“…Figura 5 -a) temperatura do painel b) pH do painel Weinberg et al (2001), citam trabalhos antigos (McDONALD et al, 1966;DICKERSON, 1988) Fornecer aos animais silagem do topo do silo, com 50% de forragem na dieta, mostrou ser a melhor estratégia de alimentação entre as variáveis avaliadas. Lechartier et al (2010), testando três diferentes inclusões de silagem de milho para vacas em lactação, perceberam que diminuindo a relação forragem: concentrado, também ocorreu aumento linear na produção de leite.…”
Section: )unclassified